The Parallelism of Serbian Constitutional Norms on the Concept and Competences of Autonomies: - Orlović, Slobodan Petar (NBP. Nauka, bezbednosti, policija, 2024)
Serbia is a decentralised unitary state comprising two territorial autonomies – the Autonomous Province of Vojvodina and the Autonomous Province of Kosovo and Metohia. The autonomies are constitutional institutions (categories), which means that their status is generally regulated by the Constitution. However, this regulation primarily concerns Vojvodina, whereas Kosovo and Metohia’s status will be determined by a special law, which will embody the constitutionally proclaimed ‘substantial autonomy’.            The Constitution determines the concept and competences of provinces through six articles, leaving the more specific regulation to the law and provincial acts. The paper critically describes this constitutional regulation, with the major remark that some provisions are redundant as they are, unacceptably, simply repeated.
Keywords: territorial autonomy, autonomous province competence, constitution, Serbia, Vojvodina, Kosovo and Metohia